Scratch line detection and restoration based on Sobel operator. (2015) - Huang, LongJun; Liu, QingHua; Tang, Jie; Li, Ping
Film movies are one of our important historical and cultural heritages. When it is stored or used, however, the film encounters many problems like scratches, dirty spots, etc. And these problems seriously affect images recorded in the film movies. To solve the problem of scratch lines, which is common on old movies, the causes of the emergence and basic features of scratch lines are analysed. After analysing the basic principles of Sobel operator, a scratch line detection and restoration algorithm based on Sobel operator is proposed. By this algorithm, we can effectively detect scratch lines on old movies and be able to get the length, and start and end positions of scratch lines and then restore the old movies. The old movies could have a better subjective visual effect after restoration.